IMPLEMENTASI METODE QUR’ANI SIDOGIRI UNTUK IMPROVING READING SKILLS AL-QUR’AN DI PONDOK PESANTREN LUBBUL LABIB AL-QUSYAIRI - Hifdil islam, Mohammad; husnah, Rif'atul (Najah: Journal of Research and Community Service, 2024)
The Qur'anic Sidogiri Method is an integrated approach to Qur'anic learning that has gained widespread attention in the world of Islamic education. This article explores the implementation of the Qur'anic Sidogiri Method and its impact at Pondok Pesantren Lubbul Labib Al-Qusyairi on improving the ability to read the Qur'an. In relevant text excerpts, K.H. Abdul Ghofur, a prominent scholar at Pesantren Sidogiri, explains that this method is not only about accurate tajweed, but also about guiding santri to feel the meaning and values contained in the Qur'ān. This holistic approach is supported by rigorous tajweed teaching, contextual understanding, and application of Qur'anic values in daily life. This article concludes that the implementation of the Qur'anic Sidogiri Method at Pondok Pesantren Lubbul Labib Al-Qusyairi provides a solid foundation for santri to read the Qur'an well and understand the sacred messages contained therein, in accordance with the vision of Sidogiri pesantren to create a generation of Muslims who are deep in the understanding and application of the Qur'an in their lives.